The Economic and Humanistic Burden of Pediatric-Onset Multiple Sclerosis - Nupur Greene; Lita Araujo; Cynthia Campos; Hannah Dalglish; Sarah Gibbs; Irina Yermilov (Journal of Health Economics and Outcomes Research, 2022)
# Background Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of the central nervous system. Pediatric-onset MS (POMS), defined as onset of MS before 18 years of age, is estimated to account for 2% to 5% of the MS population worldwide.